A systematic review and meta‐analysis of mental health service use in people who report psychotic experiences. Issue 3 (14th August 2017) - Bhavsar, Vishal; McGuire, Philip; MacCabe, James; Oliver, Dominic; Fusar‐Poli, Paolo
Abstract : Background: Self‐reported psychotic experiences (PEs) are associated with psychopathology of all kinds, not just psychoses. However, systematic reviews on the relevance of this for health services are unavailable. Furthermore, whether association with service use is confounded by other psychopathology is unknown, and is relevant to prevention and treatment. Objectives: Literature examining associations between PEs and service use was systematically reviewed. Study quality and the direction and extent of any associations were assessed, and meta‐analysis conducted. Methods: Systematic review and meta‐analysis was carried out as per PRISMA guidelines. A search of electronic databases was performed based on free‐text and structured terms. Included studies were evaluated by two raters using a structured tool and estimates extracted for reporting. Results: Thirteen studies were returned. We found two prospective studies, and a minority of studies accounted for concurrent psychopathology, limiting our ability to test our main hypotheses. Five studies reported associations by different types of service use. Almost all studies assessed service use by self‐report. Meta‐analysis suggested that people who reported PEs were around twice as likely to report service use compared to those who did not (pooled OR for all included studies: 2.20, 95% confidence intervals (95%CI): 1.66, 2.91). Conclusions: There was consistent evidence of association between PEs and mental health service use at the general population level. However, evidence for causation was poor due to a limited number of studies. Whether increased service use in this group is solely attributable to PEs, and therefore whether interventions aimed at limiting/preventing PEs might be effective, requires studies focusing on the relationships between PEs, psychopathology and service use.